Design, construction and evaluation of a device for the manufacture of ferrogram for analytical ferrography - Júnior, Anderson Inácio Junqueira; Gonçalves, Aparecido Carlos [UNESP]; Ribeiro, Victor Hugo [UNESP]; Chavarette, Fábio Roberto [UNESP]; Outa, Roberto (Wiley, 2022)
The dynamism of the reliability of machines and equipment has the objective of availability, leading to the development of several techniques of predictive maintenance, to define the ideal point for the intervention. Among the several predictive techniques, the analysis of lubricants has its highlight. In this sense, lubricants are used to reduce friction and wear between two interacting surfaces, filling the space of surface imperfections. In this way, wear is common even with the use of lubricating oils on the interacting surfaces. Thus, an artefact for ascertaining the wear particles by size in lubricating oils is analytical ferrography. In this way, this work presents the development of a low cost rotary separator prototype to obtain ferrograms, through five distinct combinations of permanent magnets and electronic devices. Several combinations of magnets were used and it was concluded that the 03, 04, and 05 combinations showed a better formation quality of ferrous wear particle rings. In addition, only two rings were formed in the 04 combination, but this was the best combination by size separation.
Keywords: analytical ferrography; lubricant analysis; predictive maintenance